Implementation of Islamic Da'wah Ethics by Islamic Boarding School Management at Darul Hikmah Narathiwat, Thailand - Nova Saha Fasadena; Amina Chuma; Siti Robi'atul Adawiyah (IJIBS, 2025)
Darul Hikmah Boarding School Narathiwat, Thailand, is an Islamic educational institution that upholds da'wah ethics as an integral part of its educational system. This research is motivated by the importance of understanding how the da'wah ethics of the management of the pesantren manifest in daily interactions with students and the surrounding community, as well as their impact on shaping the character of students who are moderate and full of compassion.This study aims to analyze the implementation of da'wah ethics by the management of Darulhikmah Boarding School in everyday interactions and to explore how these da'wah ethics influence the formation of moderate students' character, making them ready to become agents of peace in the Muslim minority community in Narathiwat.This research uses a qualitative approach (a case study design) with data collection techniques such as interviews, participatory observation, and document analysis. The research subjects include the management and students of Darulhikmah Boarding School, as well as the surrounding community. The collected data were analyzed using thematic analysis techniques to identify the patterns of da'wah ethics applied and their impact on students' character. The results of the study show that the da'wah ethics of the management of Darulhikmah Boarding School manifest in moral exemplification, gentle communication, and the enforcement of rules based on dialogue. These da'wah ethics successfully shape students who are moderate, full of compassion, and highly aware of the local socio-political sensitivity. Additionally, these da'wah ethics are implemented through a systematic institutional mechanism, with deliberation as the basis for decision-making. This research also identifies challenges related to the transition of da'wah into the digital realm, which requires strengthening media literacy and formulating clear digital da'wah ethics codes to maintain the continuity of responsible da'wah.